2023
DOI: 10.1183/16000617.0170-2022
|View full text |Cite
|
Sign up to set email alerts
|

Nonpharmacological management of psychological distress in people with COPD

Abstract: Psychological distress is prevalent in people with COPD and relates to a worse course of disease. It often remains unrecognised and untreated, intensifying the burden on patients, carers and healthcare systems. Nonpharmacological management strategies have been suggested as important elements to manage psychological distress in COPD. Therefore, this review presents instruments for detecting psychological distress in COPD and provides an overview of available nonpharmacological management strategies together wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 216 publications
0
6
0
Order By: Relevance
“…In addition, the anticipation of dyspnea itself can have a significant impact on the patient’s mood and behaviour ( 25 ), and psychological distress is prevalent in patients with COPD and is associated with a more severe course of the disease, which can also increase the burden on patients, caregivers, and the healthcare system when psychological problems are not treated ( 26 ). Therefore, more attention needs to be paid to the psychological changes caused by COPD and the impact on relatives and caregivers in the process of family rehabilitation and self-management.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the anticipation of dyspnea itself can have a significant impact on the patient’s mood and behaviour ( 25 ), and psychological distress is prevalent in patients with COPD and is associated with a more severe course of the disease, which can also increase the burden on patients, caregivers, and the healthcare system when psychological problems are not treated ( 26 ). Therefore, more attention needs to be paid to the psychological changes caused by COPD and the impact on relatives and caregivers in the process of family rehabilitation and self-management.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is also important to differentiate COPD-related anxiety from episodic, passing experiences of anxiety that can be normal reactions to events such as diagnosis or symptom exacerbation. 84 According to the conceptual model of our study, COPD-related anxiety involves persistent anxiety symptoms that are related to an individual’s processing of COPD-related internal and external factors, as well as accompanying fear-induced behavior, such as avoidance of physical activity, social distancing, and seeking hospital intervention instead of self-management. Consequently, COPD-related anxiety should be described neither as a momentary feeling nor as a mental disorder, but as a biopsychosocial pattern that develops over time and reduces an individual’s functional capacity, quality of life, and ability to cope with the illness.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few decades, there has been a growing body of literature on the influence that psychological factors can have on chronic respiratory diseases and how these, in turn, might have major implications on the psychological distress and quality of life of those affected. Over time, a strong association between increased symptoms of anxiety and depression and chronic respiratory diseases such as Chronic Obstructive Pulmonary Disease (COPD) (Vieira et al, 2011 ; Ohayon, 2014 ; Volpato et al, 2023 ), asthma (Verkleij et al, 2013 , 2017 ), Primary Ciliary Dyskinesia (PCD) (Verkleij et al, 2021a ), or Cystic Fibrosis (CF) (Quittner et al, 2016 ; Verkleij et al, 2018 ) has been documented Similarly, a strong relationship has been found between certain respiratory symptoms such as dyspnoea, wheezing or nocturnal problems and the onset of anxiety and depression (Leander et al, 2014 ). Nevertheless, many patients with chronic respiratory diseases do not meet all the diagnostic criteria for mental illness, but still experience high levels of some of their symptoms (e.g., worry, decreased mood, and loss of interest), difficulties in managing their lifestyle (e.g., disturbed sleep and lack of appetite), and other emotional reactions to their illness (e.g., shame, guilt, loneliness, and lower self-esteem) (Verkleij et al, 2018 ; Jerpseth et al, 2021 ; Noij et al, 2023 ; Volpato et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over time, a strong association between increased symptoms of anxiety and depression and chronic respiratory diseases such as Chronic Obstructive Pulmonary Disease (COPD) (Vieira et al, 2011 ; Ohayon, 2014 ; Volpato et al, 2023 ), asthma (Verkleij et al, 2013 , 2017 ), Primary Ciliary Dyskinesia (PCD) (Verkleij et al, 2021a ), or Cystic Fibrosis (CF) (Quittner et al, 2016 ; Verkleij et al, 2018 ) has been documented Similarly, a strong relationship has been found between certain respiratory symptoms such as dyspnoea, wheezing or nocturnal problems and the onset of anxiety and depression (Leander et al, 2014 ). Nevertheless, many patients with chronic respiratory diseases do not meet all the diagnostic criteria for mental illness, but still experience high levels of some of their symptoms (e.g., worry, decreased mood, and loss of interest), difficulties in managing their lifestyle (e.g., disturbed sleep and lack of appetite), and other emotional reactions to their illness (e.g., shame, guilt, loneliness, and lower self-esteem) (Verkleij et al, 2018 ; Jerpseth et al, 2021 ; Noij et al, 2023 ; Volpato et al, 2023 ). In addition, going along with polypharmacy (Ierodiakonou et al, 2021 ; Woolford et al, 2021 ), quitting smoking, using Long-Term Oxygen Therapy (LTOT) and/or Non-Invasive Ventilation (NIV) (Mehrtash et al, 2019 ; Pierucci et al, 2022 ) require changes in habits and behavior that may, in turn, contribute to the presence of distress and emotional reactions, with consequent effects on self-perception, adherence and clinical outcomes (Jerpseth et al, 2018 ; McCormick et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%